2023
DOI: 10.3390/en16083337
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Model Development for the Optimization of Water Alternating CO2 Gas for Enhanced Oil Recovery

Abstract: Optimization studies are an important task in reservoir engineering practices such as production optimization and EOR (Enhanced Oil Recovery) assessments. However, they are extensive studies with many simulations that require huge computational effort and resources. In terms of EOR, CO2 injection is one of the most common methods employed due to a high recovery potential and environmental benefits. To assess the feasibility of CO2-EOR projects, a reservoir design study must be conducted before optimization is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…To assess the reliability and performance of the developed models, several statistical indicators are commonly used. In this study, we employed three such indicators: average absolute relative deviation percentage (AARD%), determination coefficient ( ), and root mean square error (RMSE) 70 . These parameters are defined as follows, respectively: …”
Section: Resultsmentioning
confidence: 99%
“…To assess the reliability and performance of the developed models, several statistical indicators are commonly used. In this study, we employed three such indicators: average absolute relative deviation percentage (AARD%), determination coefficient ( ), and root mean square error (RMSE) 70 . These parameters are defined as follows, respectively: …”
Section: Resultsmentioning
confidence: 99%
“…The implementation of CO 2 – EOR can be done under several schemes, including the injection of miscible/immiscible CO 2 , water alternating CO 2 gas injection (WAG CO 2 ), polymer alternating gas CO 2 (PAG), simultaneous water CO 2 gas injection, foam assisted CO 2 , low salinity water–surfactant–CO 2 , and hybrid schemes with surfactant polymer (SP). Most CO 2 – EOR processes are commonly confronted to satisfy two objectives consisting of maximizing ORF and minimizing the production of CO 2 (this latter means the increase in the storage performance). However, it is worth mentioning that many published studies and experimental tests demonstrated the superiority of the miscible type (single–phase flow) of CO 2 – EOR processes in reaching higher ORF compared to the immiscible type (two–phase flow). , The suitable design of a CO 2 – EOR process depends greatly on the so-called minimum miscibility pressure (MMP) since this parameter allows the determination of the injection type, i.e., miscible or immiscible. MMP represents the cutoff pressure at reservoir temperature (T R ) above which miscibility between the reservoir fluid and the injected gas occurs after multiple contacts. …”
Section: Introductionmentioning
confidence: 99%